Determination of the Whitening Effect of Toothpastes on Human Teeth - Aydın, Numan (2021)
The desire of individuals to have whiter teeth increases the interest in tooth whitening products. Our aim was to in vitro study the whitening effect of hydrogen peroxide, blue covarine and active charcoal containing whitening toothpastes on human teeth. A total of 40 extracted human incisor teeth were used in the study. To measure the whitening effect of toothpastes, the teeth were divided into four subgroups and placed in the phantom tooth jaw model. Then, daily brushing was done with an electric toothbrush. The colors of the teeth were measured initially using the spectrophotometer (single point and bleached shade mode) and at the end of 7th, 14th and 28th days. Whitening effectiveness of toothpastes were studied according to CIEDE2000 formula (∆E00) and shade guide units (SGU). One-way analysis of variance (ANOVA) and Tukey test were used in the statistical analysis of the data. (p<0.05). Activated charcoal containing toothpaste showed the greatest whitening effect at the end of 7th, 14th and 28th days (p<0.05). There was no statistically significant difference between the whitening effects of hydrogen peroxide and conventional toothpaste (p>0.05). Blue covarine containing toothpaste had statistically the lowest whitening effect (p<0.05). All toothpastes showed a whitening effect on the teeth after 7 days of use. Activated charcoal containing toothpaste showed more whitening effect after 28 days of use than hydrogen peroxide, blue covarine and traditional toothpaste.